Structural and tribological analysis of harvester crane joint - Hedström, Gabriel (Luleå tekniska universitet, Institutionen för teknikvetenskap och matematik, 2018)
Grease-lubricated journal bearings are widely used in heavy duty applications, such as construction equipment, agriculture- and forest machines. The main purpose of the grease-lubricated journal bearing is solely to create sustainable rotation of a given application. However, purpose seldom decides complexity of journal bearing design. Depending on application, parameters such as Load , Material and Lubrication immensely increase complexity of the design. Tribology is a highly interdisciplinary subject, which requires knowledge concerning physics, chemistry, metallurgy and solid mechanics. Tribological aspects of a design are frequently regarded as irrelevant. Tribological issues are commonly enlightened in combination with structural design weaknesses. The main aim of the thesis was to analyze two cylinder joints found in a Komatsu Forest 951 crane and establish root cause to the structural and tribological issues. Outline of the approach was divided into three main targets: 1. Investigate mechanical and tribological aspects of the crane design. 2. Understand how these aspects influence the life time of the bearings. 3. Summarize the analysis and suggest improvements based on the discovery. Fundamental structural and tribological design guidelines regarding grease-lubricated journal bearings have been presented in this thesis. Damaged components such as cylinders, pins and journal bearings have been examined at Komatsu Forest’s factory in Umeå. Further, a scanning electron microscopy study has been done at Luleå University of Technology, to determine predominant wear mechanisms in the harvester crane joints. A non-linear finite element model of the crane has been designed to represent pressure distribution in the contact between bearing and pin. The finite element analysis gives a good approximation of the contact but leaves room for further refinements. Temperatures, in the contacts, have not been identified and will be measured outside the time frame of the master’s thesis. Design changes, with respect to ...